Interplay Between Notch and YAP/TAZ Pathways in the Regulation of Cell Fate During Embryo Development - Engel-Pizcueta, Carolyn; Pujades, Cristina (Frontiers in Cell and Developmental Biology, 2021)
Cells in growing tissues receive both biochemical and physical cues from their microenvironment. Growing evidence has shown that mechanical signals are fundamental regulators of cell behavior. However, how physical properties of the microenvironment are transduced into critical cell behaviors, such as proliferation, progenitor maintenance or differentiation during development, is still poorly understood. The transcriptional co-activators YAP/TAZ shuttle between the cytoplasm and the nucleus in response to multiple inputs and have emerged as important regulators of tissue growth and regeneration. YAP/TAZ sense and transduce physical cues, such as those from the extracellular matrix or the actomyosin cytoskeleton, to regulate gene expression, thus allowing them to function as gatekeepers of progenitor behavior in several developmental contexts. The Notch pathway is a key signaling pathway that controls binary cell fate decisions through cell–cell communication in a context-dependent manner. Recent reports now suggest that the crosstalk between these two pathways is critical for maintaining the balance between progenitor maintenance and cell differentiation in different tissues. How this crosstalk integrates with morphogenesis and changes in tissue architecture during development is still an open question. Here, we discuss how progenitor cell proliferation, specification, and differentiation are coordinated with morphogenesis to construct a functional organ. We will pay special attention to the interplay between YAP/TAZ and Notch signaling pathways in determining cell fate decisions and discuss whether this represents a general mechanism of regulating cell fate during development. We will focus on research carried out in vertebrate embryos that demonstrate the important roles of mechanical cues in stem cell biology and discuss future challenges.